Strategies for Reuse of Skins Separated From Grape Pomace as Ingredient of Functional Beverages - Gerardi, Carmela; D'amico, Leone; Migoni, Danilo; Santino, Angelo; Salomone, Antonio; Carluccio, Maria A.; Giovinazzo, Giovanna (Frontiers in Bioengineering and Biotechnology, 2020)
Wine grape pomace, the by-product of wine making, is a source of polyphenols, metals, and organic acids, and may be exploited for the production of functional beverages. Among red wines, Primitivo and Negramaro varieties possess an interesting amount of polyphenolic compounds and other chemicals. Consequently, study of the biological activity of Primitivo and Negramaro vinification by-products is of great interest as well as optimizing the extraction of its bioactive components. In order to stabilize the grape pomace, different methods of drying grape pomace were tested. After stabilization of the pomace, the grape skins were manually separated from the seeds and any woody parts. The chemical characterizations of acidified alcoholic (methanol/ethanol) and water extracts and either microwave-assisted or ultrasound-assisted extractions of separated grape skins were compared. Besides that, the in vitro antioxidant activity of wine pomace skin extracts was also investigated as Trolox equivalents antioxidant capacity (TEAC) and oxygen radical absorbance capacity (ORAC). Overall, the alcoholic extractions were found to be the most effective for recovering phenolic compounds, when compared with those in water. Ultrasound- and microwave-assisted extraction of pomace skin using acidified water allowed the highest TEAC value. Taking into account the water extraction result, in order to reuse grape pomace skins to produce a functional beverage, we utilized them in combination with black tea, karkadè (Hibiscus sabdariffa L.), or rooibos (Aspalathus linearis Burm.) to produce an infusion. The combination of grape skins and black tea showed the highest ratio of total phenol content to antioxidant activity. Moreover, skin isolated from pomace, with or without black tea infusions, were shown to have anti-inflammatory capacity in human cell culture. Our results raise the value of grape skin pomace as a rich source of bioactive compounds with antioxidant and anti-inflammatory activity and suggest its exploitation as an ingredient for functional beverages.